Pemberdayaan Pupuk Dari Limbah Kulit Pisang Desa Larangan Jambe Kecamatan Kertasmaya Kabupaten Indramayu - Agus Yudianto; Meddy Nurpratama; Taufansyah Firdaus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Community Service Program (PKM) activities are carried out starting with village observations, program planning, consultation on the planned program with the village, local MSME owners, school head and the implementation of the planned program. PKM activity programs have been implemented. The results obtained through the implementation of the PKM work program brought about changes in the processes of MSMEs in Larangan Jambe village, as well as a reduction in the amount of banana peel waste from Canvendish Banana MSMEs, their conversion process into compost as well as behavioral change analysis to change adverse behaviors, as well as educate people about employment through legal procedures and create favorable conditions for going abroad, as well as solve the problem of littering and maintain irrigation systems for rice fields so that they are cleaner and better maintained, and provide information to the people of Larangan Jambe village. Overall, the individual programs can work well and contribute to the future progress of the Larangan Jambe village community. The PKM program is not only training and learning material for the Larangan Jambe village community but also a value transfer. It is hoped that the existence of the PKM agenda can bring about changes as part of efforts to promote village development and empowerment.